Utilization of Sludge Waste as Fertilizer for Chili Plants: Observed from Technical, Economical Aspects and Farmers’ Perceptions - Arifianto, Aditya; Budianto, Agus (International Journal of Environment, Agriculture and Biotechnology, 2019)
PT. X was an industrial company that engaged in chicken slaughterhouse and meat processing and its derivatives, with a continuous production process that produced a variety of waste ranging from Liquid, Solid, and others. Moreover, for the type of liquid waste produced by PT. X, was treated with a Wastewater Treatment Plant which was one of the facilities in PT. X. The second stage was to make a comparison between Sludge, chicken manure, and rice husk. Furthermore, there was a variation of the ratio: the first 1: 1: 1 and the second 2: 1: 1 where two were the number of sludge. Application of fertilizers was carried out on chili plants. From the test results, it showed that there was an increase in productivity between 30% - 42.8% in chili plants. Therefore, the cost of fertilizing in one crop of chili with compost processed by Sludge IPAl of PT. X was equal to Rp. 1,500 per stem in a single planting period. As for the NPK Mutiara fertilizer, the cost incurred for fertilizing in a single chili planting period was Rp. 4,050, - per stem of chili plants. While the result of the questionnaire towards the attitudes of farmers showed sufficient value, hence, the fertilizer processed by IPAL sludge had a good chance to be accepted by the community, especially chili farmers.